An Old Norse Courtly Analogue to Beowulf. - Hobson, Jacob (Neophilologus, 2019)
This article identifies a new Old Norse analogue to Beowulf's battle in the mere: an episode narrated in chapters 195–197 of the courtly thirteenth-century text Þiðreks saga af Bern. It describes and examines the resemblances between this episode and Beowulf's fight against Grendel's mother, as well as the notorious analogue of Grettir's fight against a troll-woman. As I hope to show, several details of the scene in Þiðreks saga make it a particularly strong analogue to the second monster fight in Beowulf. This article situates these analogues against the common Old Norse topoi of moundbreaking and land-cleansing in order to separate what is analogous from what is merely saga convention. The analogue in Þiðreks saga reveals the broad circulation and flexible use of the monster-fighting narrative in medieval Germanic literature, a narrative paradigm that sometimes attaches to legendary figures but appears to circulate independently of them.